lncRNA ZEB1-AS1 Mediates Oxidative Low-Density Lipoprotein-Mediated Endothelial Cells Injury by Post-transcriptional Stabilization of NOD2 - Xu, Xiaohui; Ma, Congmin; Duan, Zhihui; Du, Yanjiao; Liu, Chao (Frontiers in Pharmacology, 2019)
Oxidized-low density lipoprotein (ox-LDL) can induce injury of endothelial cells, causing atherosclerosis, which is an important initial event in several cardiovascular diseases. Long noncoding RNAs (lncRNAs) have emerged as regulators of diverse biological processes, but their specific biological functions and biochemical mechanisms in ox-LDL-induced endothelial cell injury have not been well investigated. Here, we describe the initial functional analysis of a poorly characterized human lncRNA ZEB1 antisense 1 (ZEB1-AS1). We found that ox-LDL treatment could induce a decreased cell viability and an increased cell apoptosis in endothelial cells, and knockdown of ZEB1-AS1 significantly reversed this effect. Mechanistically, ox-LDL treatment could sequester p53 from binding to ZEB1-AS1 promoter region, causing transcriptional activation and upregulation of ZEB1-AS1. Moreover, enhanced ZEB1-AS1 could upregulate Nucleotide-Binding Oligomerization Domain 2 (NOD2) expression through recruiting leucine-rich pentatricopeptide repeat motif-containing protein (LRPPRC) to stabilize NOD2 mRNA. Experimental data showed that knockdown of NOD2 or LRPPRC dramatically abrogated the functional role of ZEB1-AS1 in ox-LDL-induced endothelial cell injury. In summary, we demonstrated that lncRNA ZEB1-AS1 regulates the ox-LDL-induced endothelial cell injury via an LRPPRC-dependent mRNA stabilization mechanism. Therefore, ZEB1-AS1 may serve as a multi-potency target to overcome endothelial cell injury, atherosclerosis and other cardiovascular diseases.